Vai trò trung gian của mô hình AMO trong mối quan hệ giữa hệ thống làm việc hiệu suất cao và kết quả kinh doanh - Bui Thi Phuong , Linh; Tran Kim , Dung (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
The purpose of this paper is to measure the impact of high performance work systems (HPWS) on business performance in banks. Survey data were obtained from 386 transaction offices, bank branches within 17 Stock Commercial banks in Ho Chi Minh city and was processed with Smart PLS-SEM 3.3.3. The results indicated the mediator role of the service-oriented AMO model (service ability, customer orientation, and service climate) between HPWS and business performance of bank branches. Results also indicated the moderator role of dynamic environment between HPWS and business performance. Practical implications regarding banks investing in HPWS and service ability to elicit higher business performance are also discussed.